A Case of Reverse Takotsubo Cardiomyopathy Incited by a Spinal Subdural Hematoma - Kyle Sanchez; Steven Glener; Nathan E. Esplin; Okorie N. Okorie; Amay Parikh (Case Reports in Neurological Medicine)
Takotsubo cardiomyopathy is a rare syndrome of transient, reversible left ventricular systolic dysfunction. It mimics myocardial infarction clinically and includes elevated cardiac enzymes, but echocardiography reveals apical ballooning and basal hyperkinesis. Infrequently, midventricular or even reverse Takotsubo patterns have been described, involving ballooning of the basal heart without the characteristic ‘Takotsubo’ appearance. There are cases in the literature that support a connection between reverse Takotsubo cardiomyopathy (r-TTC) and neurological insults as inciting factors. We report a case of r-TTC in an otherwise healthy 23-year-old man presenting with back pain, urinary retention, bradycardia, and hypertension. Troponin levels and brain natriuretic peptide (BNP) were elevated, and echocardiogram revealed an ejection fraction (EF) of less than 20%. In addition, MRI demonstrated a spinal subdural hematoma from T1-S1 with no cord compression. Repeated echocardiogram demonstrated an EF of 20-25% with a reverse Takotsubo pattern of cardiomyopathy. With supportive care, his clinical picture improved with normalization of cardiac enzyme and BNP values. This case represents a r-TTC presenting as heart failure in a young, apparently healthy male likely incited by a spinal subdural hematoma. To our knowledge, it is the first of its kind reported.